OBJECTIVE AND MORALIST CRITICIS THE WAY OF WATER - Okta Viani Dwi Lestari; Ika Oktaria Cahyaningrum; Titis Ary Laksanti I Desak Ketut (PT Akselerasi Karya Mandiri, 2025)
This research aims to analyze the objective and moralist criticism of James Cameron's Avatar 2: The Way of Water. This analysis will focus on two main aspects, namely objective criticism and moralist criticism. Objective criticism examines objective elements in literary works such as theme, plot, characters and characterization, setting, point of view and message. Meanwhile, moralist criticism examines the moral values contained in the film scenes. Using descriptive qualitative methods, researchers can describe and interpret in detail how objective criticism and moralist criticism are represented in the film Avatar 2: The Way of Water. In two categories of criticism analyzed from the movie Avatar 2: The Way of Water, namely Objective Criticism and Moralist Criticism. In Objective Criticism, 18 data were found with the following data distribution: theme (4 data), setting (4 data), character and characterization (2 data), plot (2 data), point of view (2 data), and message (4 data). Moralist Criticism includes a total of 21 data, with the following details: criticism of natural exploitation and environmental damage (5 data), colonialism and bullying (4 data), lives destroyed by military policy and violence (3 data), family sacrifice and responsibility (4 data), ignoring the environment and destroying ecosystems (3 data), and the struggle to preserve cultural heritage (2 data). In terms of percentage, Objective Criticism contributes 46% of the total 39 data analyzed, while Moral Criticism contributes 54%, in Avatar 2: The Way of Water.